Exploring Deixis in Taylor Swift's Song 'Cardigan': A Descriptive Qualitative Analysis - S, Kartika (Cipta Pustaka Nusantara, 2024)
This study explores the use of deixis—a pragmatic linguistic concept of context-dependent expressions—in Taylor Swift's song